Penggunaan Chatbot pada Sistem Informasi Buku Berbasis Web Menggunakan Metode Natural Language Processing (NLP) - m.rezki hamdani iki; Nurjayadi; Unang Rio; Muhamad Jamaris (BETRIK, 2026)
Advances in information technology require fast and effective information retrieval services, including in library book information systems. Manually searching for books in catalogs is often timeconsuming and slow to respond, especially as the number of books in libraries increases. This problem highlights the importance of creating an automated system that can provide information directly and timely. This research aims to create a web-based chatbot that can provide information about books, using Natural Language Processing (NLP) techniques to make information retrieval more effective. The research method includes analyzing system requirements, designing the system structure, implementing a natural language processing model with text preprocessing steps such as tokenization, case adjustment, and stemming, and testing the system's capabilities. The system was developed using a prototype method to suit user needs. Evaluation was conducted by testing the accuracy of answers and checking the level of user satisfaction. Testing showed that the chatbot can provide information about the title, author, publisher, year of publication, and location of a book with a 90% accuracy rate, measured by the extent to which the answers provided by the  chatbot match the user's questions. Furthermore, user test results indicate that this method is more efficient in saving search time than previous methods. So the use of NLP-based chatbots has been proven to help improve the quality and speed of providing information about books in libraries.